Diffusing Chinese rice technology in rural Tanzania: Lessons from the Dakawa agro-technology demonstration center - Hezron Makundi (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2017)
This paper by Hezron Makundi uses empirical evidence from the Dakawa center in Tanzania to examine the role of agro-technology demonstration centers in diffusing selected agro-technologies to local farmers. The Dakawa center has struggled to balance the goal of technological diffusion with other interests, most notably the manifestation of China's soft power and its commercial goal of operating a financially self-sustaining farm. Yet, despite these broad ambitions, the center has managed to contribute a great deal towards multi-actor efforts to lessen the information and knowledge barriers hindering the adoption of improved rice farming technology by farmers in Dakawa.
Keywords: 330